Governance in Nunavut - Cozzetto, Donald Arthur (Virginia Tech, 1990)
The settlement of aboriginal claims has been on the northern policy forefront for the past two decades. At long last the settlement of these claims may be imminent. This dissertation examines a series of political-administrative strategies designed to assist in establishing a Native form of governance in light of the recent signing of the agreement-in-principle respecting aboriginal claims settlements in Nunavut, the Inuit territory in northeastern Canada. To date, research directed in the area of Native claims primarily focuses upon normative and legal foundations for the claims, the unique cultural and environmental dimensions, and the quantification of actual entitlements in the form of cash and land transfers. However, the critical and complex area of post-claims models of governance has largely been ignored. Drawing upon the public administration literature as a theoretical base, I explore a number of models that provide a means through which the distinctive aspects of aboriginal society, economy, and culture, can be maintained, while at the same time recognizing the need for continued active Native participation in the Canadian federation. In particular, primary research conducted in northern Canada serves as the catalyst for the ensuing discussion. In addition, a comparative methodology is used to highlight the negative experiences of the Alaska claims settlement, the experiences of other Canadian Native groups, and models adopted in other parts of the world. Ph. D.